Transient spray combustion characteristics in a gas–liquid pintle rocket engine under acoustic excitation - Xuan Jin; Chao Zhu; Dejiang Chen; Zhongpei Zhang (Scientific Reports)
Abstract In order to investigate the acoustic oscillation characteristics of gas–liquid pintle rocket engines and elucidate the path by which spray combustion process provides energy to the combustor pressure oscillation, a LOX/GCH4 pintle engine with rectangular combustor was designed. By adding transverse velocity disturbance for the first time, the acoustic response of spray combustion process was simulated, and the effect of excitation amplitude on acoustic response was researched. Numerical results show that the adopted transverse velocity disturbance can excite the first-order transverse acoustic oscillation with same excitation frequency in the engine combustor. The acoustic response maintenance mechanism under extrinsic excitation is summarized for pintle engines. Besides, the temperature distribution inside the engine combustor tends to be uniform, and the low-frequency oscillation caused by the flame transverse swing gradually disappears. The amplitude of combustor pressure oscillation is dominated by excitement amplitude and phase difference between the pressure and heat release in combustion reaction region. In addition, the time-averaged combustor pressure can be amplified mainly by transverse velocity disturbance. The research work can provide a reference for related fire tests on the acoustic response of a subscale gas–liquid pintle engine.